Manajemen ARISTA Sport Center Di Ungaran Tahun 2018 (Universitas Negeri Semarang, 2021)
The purpose of this study was to determine the management of Arista Sport Center in Ungaran in 2018. This research uses a qualitative approach with descriptive methods. The location of this research was conducted at the Arista Sport Center in Ungaran, namely in Jalan Merdeka, Langensari Village, Ungaran Barat District. The research objectives of this research are managers, employees and visitors. The research instruments used were observation, interviews, and documentation. Checking the validity of the data used using triangulation. Data analysis uses data reduction, data display, and conclusion drawing data. Research and discussion results show, 1) Planning management at the Arista Sport Center has been running in the provision of its facilities and has the same objectives, namely doing business and facilitating futsal and badiminton sports at the Arista Sport Center, 2) Arista Sport Center organizational management still does not have an organizational structure so that there is a dual function of employee duties, 3) management of the facilities at the Arista Sport Center, there is already communication between the manager and the employees, then the employees and customers are running well. In addition, communication also functions as a promotional effort to attract customers, and 4) Supervising management at the Arista Sport Center, the manager always monitors both employee performance and customer interest (members). Based on the results of the research and discussion obtained, it can be concluded that the management of the Arista Sport center in Ungaran in 2018 has gone as expected by the manager based on the management function.